Pilot’s assessment of the Vietnam provincial innovation index - Hoang Minh; Nguyen Thi Phuong Mai; Nguyen Vo Hung (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The Global Innovation Index (GII) of the World Intellectual Property Organization (WIPO) has been used by the Viet Nam Government since 2017 as a management toolkit for various ministries and agencies. As this index operates at the national level, thus authorities at provincial level have not yet played a role in improving Viet Nam's GII index. Provincial authorities with different characteristics require tailored solutions and socio-economic development models based on science, technology and innovation (STI). Establishing a provincial-level innovation index will provide a practice and comprehensive overview of the status of the socio-economic development model based on STI in each locality, offering evidence of strengths, weaknesses, potential factors, and necessary conditions to promote socio-economic development based on STI, thereby contributing to the nation's GII improvement. Building this provincial -level innovation index involves several steps, and the pilot assessment is expected to provide insights and foundations for the formal construction and implementation of this toolkit in the coming time. This article presents the results of the pilot’s assessment on the local-level innovation index conducted in 2021-2022, covering 18 localities based on the GII index framework and methodology. Code: 23101701